A randomised controlled feasibility trial of vitrectomy versus laser for diabetic macular oedema. Issue 1 (21st December 2004) - Thomas, D; Bunce, C; Moorman, C; Laidlaw, D A H
Abstract : Aim: (1) To evaluate whether vitrectomy is preferable to further macular laser in improving visual acuity and resolving retinal thickening in patients with diabetic macular oedema (DMO) despite previous laser and no macular traction. (2) To determine the feasibility of further trials in this population in terms of magnitude of comparative clinical effect, rate of recruitment, and loss to follow up. Methods: A randomised controlled feasibility study. Patients with DMO and a visual acuity of 0.3 logMAR (6/12) or worse after one or more macular laser treatments were randomised on a 1:1 basis to either pars plana vitrectomy (PPV) with internal limiting membrane (ILM) peeling or further macular laser. Patients with a posterior vitreous detachment, biomicroscopic evidence of retinal traction, or a taut thickened posterior hyaloid (TTPH) were excluded. Primary outcome measures were (1) best corrected logMAR visual acuity, (2) mean central macular thickness on optical coherence tomography, and (3) rate of recruitment and loss to follow up. Analysis was on an intention to treat basis. Results: 19 patients were randomised to PPV and 21 to further macular laser. The mean baseline logMAR visual acuity was 0.65 (SD 0.28) for the group randomised to PPV and 0.60 (0.23) for the group randomised to laser. The mean change in best corrected visual acuity of the vitrectomy group was deterioration by 0.05 logMAR, while in the control group the mean change was an improvement of 0.03 logMAR. The median (interquartile range) baseline central macular thickness was 403 (337, 492) for the group randomised to PPV and 387 (298, 491) for the controls randomised to laser. The median change in central macular thickness from baseline to review in the vitrectomy group was a thinning by 73 μm (20%) and by 29 μm (10.7%) in the control laser group. This single centre was able to recruit 40 patients in 18 months with follow up of 82% at 1 year. Conclusion: A randomised controlled trial was found to be potentially feasible in this population, the rate of recruitment was however slow and one in five patients were lost to follow up because of death and ill health. These data provide little evidence in terms of visual acuity and macular thickness of any benefit of vitrectomy over further macular laser in patients with an attached hyaloid, DMO despite previous laser, and no clinically evident macular traction or TTPH.